FINANCIAL REPORT PREPARATION TRAINING FOR RT (NEIGBOHOOD UNIT) DEVICES IN RW (HAMLET UNIT) ENVIRONMENT 16 BAROS CITY CIMAHI VILLAGE: FINANCIAL REPORT PREPARATION TRAINING FOR RT (NEIGBOHOOD UNIT) DEVICES IN RW (HAMLET UNIT) ENVIRONMENT 16 BAROS CITY CIMAHI VILLAGE - Kharaningrum Mulyanti; Riani Tanjung; Yohanes Casmadi (PPM Universitas Logistik dan Bisnis Internasional, 2018)
A good governance system is not only a responsibility that must be carried out by the central government, Neighborhood association as the smallest social institution even responsible for implementing the good governance. One form of implementation can be implemented in the form of financial statements in the area. The implementation of good governance has not been fully realized in all RT neighborhoods in Cimahi City, one of them in RW 16, Baros Village. The Community Service activities are expected to increase the awareness of the neighborhood administrators to prepare financial reports in accordance with the rules of simple government accounting standards. The methods used in this activity include lectures, tutorials, and discussions. This PKM activity went well and got good enthusiasm from the RT administrators, and it was hoped that this activity would be the beginning of the implementation of a good governance system. Sistem pemerintahan yang baik bukan hanya tanggung jawab yang harus diemban oleh pemerintah pusat, Rukun tetangga sebagai Lembaga kemasyarakatan terkecil sekalipun bertanggung jawab dalam pelaksanaan good governance tersebut. Salah satu bentuk dari pelaksanaannya dapat diimplementasikan dalam bentuk pelaporan keuangan yang ada di area-nya. Pelaksanaan good governance belum sepenuhnya terwujud di seluruh lingkungan RT di Kota Cimahi, salah satunya di RW 16 Kelurahan Baros. Kegiatan Pengabdian Kepada Masyarakat ini diharapkan dapat meningkatkan kesadaran para pengurus RT untuk menyusun laporan keuangan sesuai dengan kaidah standar akuntansi pemerintahan yang sederhana. Metode yang digunakan dalam kegiatan ini meliputi ceramah, tutorial, dan diskusi. Kegiatan PKM ini berjalan lancar dan mendapatkan antusias yang baik dari para pengurus RT, dan diharapkan kegiatan ini menjadi awal dari terlaksananya sistem pemerintahan yang baik